The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.jpowsour.2014.03.114
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of sulfate ions and protons to the specific capacitance of microporous carbon monoliths

Abstract: The monoliths studied in this work show large specific surface areas (up to 1600 m 2 g -1 ), high densities (up to 1.17 g cm -3) and high electrical conductivities (up to 9.5 S cm -1 ). They are microporous carbons with pore sizes up to 1.3 nm but most of them below 0.75 nm. They also show oxygen functionalities. The electrochemical behavior of the monoliths is studied in three-electrode cells with aqueous H 2 SO 4 solution as electrolyte. This work deals with the contribution of the sulfate ions and protons t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
(118 reference statements)
1
3
0
Order By: Relevance
“…In a previous study, the EDLC performances of the monoliths revealed high capacitances on a gravimetric, and exceptionally high capacitances on a volumetric basis . In a further study, the contribution of sulfate ions and protons to the specific capacitances have been studied in more detail . In the present work, these values are confirmed, comparing the results obtained in two‐ and three‐electrode configurations.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…In a previous study, the EDLC performances of the monoliths revealed high capacitances on a gravimetric, and exceptionally high capacitances on a volumetric basis . In a further study, the contribution of sulfate ions and protons to the specific capacitances have been studied in more detail . In the present work, these values are confirmed, comparing the results obtained in two‐ and three‐electrode configurations.…”
Section: Introductionsupporting
confidence: 79%
“…The specific capacitances of CM, CM‐N 2 , CM‐24, and CM‐48 are given in Table . The results were obtained from galvanostatic measurements in symmetric two‐electrode cells ( C s,2ec ) and three‐electrode cells ( C s,3ec ) for a low current density of 1 mA/cm 2 , that is, in nearly steady conditions . It can be observed that the values obtained in the two different setups are in very good agreement.…”
Section: Resultsmentioning
confidence: 91%
“…In the literature, including a previous paper of some of the present authors, oftentimes SO 4 2− and H 3 O + are reported as the dominant ions for the aqueous solution of sulfuric acid . However, this is inaccurate due to the fact that the dissociation of sulfuric acid in water involves two stages.…”
Section: Resultsmentioning
confidence: 75%
“…Advanced analyses of the isotherms based on Density Functional Theory (DFT) [4,81,82] have been proposed to provide areas taking into account the ions dimensions [83][84][85]. With the help of the software of commercial adsorption equipments, the pore size distribution of nanoporous carbons is assessed and, subsequently, the surface area involved in charge storage is calculated by subtracting that in pores smaller than the ions size.…”
Section: Surface Area Accessible To Electrolyte Ionsmentioning
confidence: 99%